Graft-versus-tumor effect of post-transplant cyclophosphamide-based allogeneic hematopoietic cell transplantation - Nakamae, Hirohisa (Frontiers in Immunology, 2024)
Post-transplant cyclophosphamide (PTCy) is expected to become the new international standard for graft-versus-host disease prophylaxis, not only in HLA-haploidentical transplantation, but also in HLA-matched transplantation. However, concerns about the harmful impact of PTCy on the graft-versus-tumor (GVT) effect have not yet been completely dispelled. Therefore, it is urgently needed to establish a strategy to induce the GVT effect more effectively in allogeneic hematopoietic cell transplantation (allo-HCT) using PTCy as a platform. This review comprehensively surveys and explains the effect of PTCy with a focus on the GVT effect, and may contribute to developing effective strategies for PTCy-based allo-HCT.